The Borges of Borges: the Construction of a Particular Otherness - Calderón Sánchez, Estefanía (2023)
The work of the Argentinian Jorge Luis Borges marked a milestone in literary history, given that he questioned many of the precepts inherited from the European tradition by formulating a poetics in which ambiguity, parody and instability are intrinsic parts of his literary perspective. For this reason, this article will focus on one of the Argentinean's most recurrent themes: otherness, which not only allows us to talk about a particular literary construction, but also to approach the figure of a writer who unfolds and reveals himself in his texts. Thus, the texts to be analyzed are part of two of the Argentinean's most important productions. On the one hand, "The Theologians" and “Averroes's Search” belong to the book The Aleph (1949) and, on the other, “The Other” is one of the stories in The Book of Sand (1975). All three have been widely cited by literary critics; however, no study has been found where a dialogue between them has been established. Therefore, the present analysis seeks to construct a perspective that will enrich the discussion on otherness and its relation to the themes of the double and identity within Borge’s world.